2016
DOI: 10.1117/1.oe.55.6.066109
|View full text |Cite
|
Sign up to set email alerts
|

Ultraflat-top midinfrared coherent broadband supercontinuum using all normal As 2 S 5 -borosilicate hybrid photonic crystal fiber

Abstract: Ultraflat-top midinfrared coherent broadband supercontinuum using all normal As 2 S 5 -borosilicate hybrid photonic crystal fiber," Opt. Eng. 55(6), 066109 (2016), Abstract. We report more than two octave spanning mid-IR flat-top supercontinuum (SC) generation using all normal As 2 S 5 -borosilicate hybrid photonic crystal fiber. Our design is based on a chalcogenide As 2 S 5 photonic crystal fiber (PCF), where the first ring composed of six air holes is made by borosilicate glass. By injecting 50-fs pulses wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 25 publications
(33 reference statements)
0
10
0
Order By: Relevance
“…Consequently, highly coherent SCs can be obtained from such fibers. Coherent SCs based on ChG fibers with ANDi profiles have been reported in several experiments and simulations [140,143,168,169]. Liu et al [168] used a ChG MOF with a core material of AsSe 2 and four air holes replaced by As 2 S 5 glass rods to engineer the dispersion to ANDi.…”
Section: Coherent Sc Sources Based On Chg Fibersmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, highly coherent SCs can be obtained from such fibers. Coherent SCs based on ChG fibers with ANDi profiles have been reported in several experiments and simulations [140,143,168,169]. Liu et al [168] used a ChG MOF with a core material of AsSe 2 and four air holes replaced by As 2 S 5 glass rods to engineer the dispersion to ANDi.…”
Section: Coherent Sc Sources Based On Chg Fibersmentioning
confidence: 99%
“…Besides tellurite glasses, borosilicate glasses have also been used as cladding materials of MOFs. Salem et al [143] numerically reported MIR SC generation from 1 to 5 µm in an As 2 S 5 -borosilicate MOF.…”
Section: Sc Generation In Chg Mof Fibersmentioning
confidence: 99%
“…According to previous studies, a high degree of coherence is accessible in waveguides with all-normal dispersion. [59,60] The noise sensitivity associated with input pulse is investigated through the degree of coherence introduced by Equation ( 8).…”
Section: The Proposed Structure and Principlesmentioning
confidence: 99%
“…Although the comparison is performed by considering a spectral flatness of 20 dB level, it reveals the potential of our proposed Ga 8 Sb 32 S 60 ChG glass based PCF to generate coherent, broadband and ultra-flat SC spectra. Also, it is worth noting that the SC is generated in our PCF with a simple design compared to more complex structures such as multi-material PCFs [19,22], PCF with different air holes diameters [17] or nanostructured graded-index fiber [43].…”
Section: Simulation Of Mid-infrared Sc In the Proposed Pcfmentioning
confidence: 99%
“…They have numerically shown that coherent SC spectrum extending from 2.9 to 4.575 m at a 3 dB spectral flatness level can be achieved by launching a 0.05 nJ energy laser pulses pumped at a central wavelength of 3.7 m into a 5 cm ANDi PCF length. A. Ben Salem et al reported SC generation in a kind of hybrid PCF composed of As 2 S 5 ChG glass and borosilicate [19]. The authors have shown that coherent and ultra-flat SC spectra spanning from 1 to 5 m can be obtained by injecting at 2.5 m, 50 fs pulses with 28.16 kW peak power through 4 mm PCF length.…”
Section: Introductionmentioning
confidence: 99%